Critical determinants of combined sprint and endurance performance: an integrative analysis from muscle fiber to the human body - van der Zwaard, S.; van der Laarse, W. J.; Weide, G.; Bloemers, F. W.; Hofmijster, M. J.; Levels, K.; Noordhof, D. A.; de Koning, J. J.; de Ruiter, C. J.; Jaspers, R. T. (The FASEB Journal, 2018)
Optimizing physical performance is a major goal in current physiology. However, basic understanding of combining high sprint and endurance performance is currently lacking. This study identifies critical determinants of combined sprint and endurance performance using multiple regression analyses of physiologic determinants at different biologic levels. Cyclists, including 6 international sprint, 8 team pursuit, and 14 road cyclists, completed a Wingate test and 15-km time trial to obtain sprint and endurance performance results, respectively. Performance was normalized to lean body mass2/3 to eliminate the influence of body size. Performance determinants were obtained from whole-body oxygen consumption, blood sampling, knee-extensor maximal force, muscle oxygenation, whole-muscle morphology, and muscle fiber histochemistry of musculus vastus lateralis. Normalized sprint performance was explained by percentage of fast-type fibers and muscle volume (R2 = 0.65; P < 0.001) and normalized endurance performance by performance oxygen consumption (Vo2), mean corpuscular hemoglobin concentration, and muscle oxygenation (R2 = 0.92; P < 0.001). Combined sprint and endurance performance was explained by gross efficiency, performance Vo2, and likely by muscle volume and fascicle length (P = 0.056; P = 0.059). High performance V?o2 related to a high oxidative capacity, high capillarization × myoglobin, and small physiologic cross-sectional area (R2 = 0.67; P < 0.001). Results suggest that fascicle length and capillarization are important targets for training to optimize sprint and endurance performance simultaneously.